Preparation of Poloxamer188-b-PCL and Study on in vitro Radioprotection Activity of Curcumin-Loaded Nanoparticles - Lin, Xiaona; Shi, Yongli; Yu, ShaSha; Li, Siyi; Li, Wenhui; Li, Meishuang; Chen, Shengxi; Wang, Yuanbo; Cong, Mei (Frontiers in Chemistry, 2020)
A novel polymer of poloxamer188-b-PCL was synthesized via a ring-opening polymerization. Fourier transform infrared spectroscopy (FTIR), Raman, and 1H nuclear magnetic resonance (1H NMR) spectra were used to study the structures of obtained poloxamer188-b-PCL. The thermo-stability of poloxamer188 -b-PCL was carried out with thermal gravimetric analyzer (TGA), and cytotoxicity was obtained by CCK8 method. Cargo-free and curcumin (CUR)-loaded poloxamer188-b-PCL NPs were fabricated via solvent evaporation method. The morphology, particle size distribution, and stability of cargo-free NPs were studied with scanning electron microscope (SEM) and laser particle analyzer. The in vitro radioprotection activity of CUR-loaded NPs was performed. FTIR, Raman, and 1H NMR spectra confirmed the obtaining of poloxamer188-b-PCL. TGA curves suggested poloxamer188-b-PCL had better thermo-stability than original poloxamer188. Cell tests suggested that the cargo-free NPs had no cytotoxicity. SEM image showed that the cargo-free NPs were spherical with a diameter of 100 nm. Free radical scavenging experiments proved that CUR-loaded NPs had better antioxidant activity than CUR solutions. CUR-loaded NPs could be detected in all tissues, including liver, kidneys and lung. In summary, this work demonstrated a feasibility of developing an injective formulation of CUR and provided a protection agent in caner radiotherapy.